1992
DOI: 10.1097/00000658-199204000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Biliary IgA After Burn Injury

Abstract: The concentration of biliary IgA is greatly reduced after scald burn injury in the rat, thereby contributing to a deficiency in upper intestinal immune defense. This reduction in biliary IgA might have several explanations, including failure of the transhepatic transport of polymeric IgA (pIgA) from the circulation, decreased delivery of pIgA to the hepatocyte, or decreased local synthesis of IgA in the liver. The authors examined whether burn injury reduces circulating pIgA available for delivery to the hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…The intestinal IgA levels appear to be associated with the local immunological dysfunction [38][39][40][41] . The change in intestinal pHi showed that intestinal hemorrhagic injury may result in the release of intestinal mucosal enzyme, subsequently leading to significant elevation of plasma DAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal IgA levels appear to be associated with the local immunological dysfunction [38][39][40][41] . The change in intestinal pHi showed that intestinal hemorrhagic injury may result in the release of intestinal mucosal enzyme, subsequently leading to significant elevation of plasma DAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…En general, se considera que son necesarios todos estos factores para que la translocación bacteriana llegue a producirse. El sobrecrecimiento bacteriano intestinal desempeña un papel muy importante en la patogenia de la translocación bacteriana 2,10,11,14 y estaría favorecido por diversos factores como las alteraciones en los mecanismos de defensa inmunológica locales 15,16 , la disminución en la motilidad intestinal 13 , la administración prolongada de antibióticos que determinaría el sobrecrecimiento de bacterias resistentes 17,18 o la malnutrición 2 . Entre los mecanismos de defensa inmunológica locales frente al desarrollo de translocación bacteriana son de especial importancia las placas de Peyer, los linfocitos y macrófagos de la pared intestinal y la producción de IgA local y excretada con la bilis 1 .…”
Section: Patogenia De La Translocación Bacterianaunclassified
“…Entre los mecanismos de defensa inmunológica locales frente al desarrollo de translocación bacteriana son de especial importancia las placas de Peyer, los linfocitos y macrófagos de la pared intestinal y la producción de IgA local y excretada con la bilis 1 . En este sentido, se ha observado una disminución de la producción de IgA en la bilis de ratas con quemaduras 16 y en el intestino de pacientes con cirrosis alcohólica 15 , que podría contribuir al desarrollo de translocación bacteriana en estas situaciones. A nivel sistémico, se han descrito múltiples alteraciones en los mecanismos de defensa inmunológica 1,11 en las diferentes situaciones en que se produciría la translocación bacteriana, destacando la disminución en la actividad del sistema reticuloendotelial 19 , la disfunción en la actividad fagocítica de los neutrófilos 20 y la disminución en la concentración de diversas proteínas del suero con actividad opsónica 1,21 .…”
Section: Patogenia De La Translocación Bacterianaunclassified